President Elections Mechanism: Comparative Studies from Indonesia, Russia, and Türkiye (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the differences and similarities in the presidential election system in 3 (three) countries, as an example we choose Indonesia, Russia, and Türkiye. This research focuses on how the presidential election system is implemented in the countries of Indonesia, Russia, and Türkiye as well as, what are the differences in the presidential election system used, the pattern of nominations, and the requirements for presidential nominations by the countries of Indonesia, Russia, and Türkiye. This study uses a normative juridical method with a statutory approach and a comparative approach based on the constitution of each country. The results of the study show that there are similarities and differences in the presidential elections in the three countries. First, the similarity of the three countries is implementing a plural or district system with the Two Round System variant. The winner of the election must get absolute or absolute votes. Second, the differences between the three countries in presidential elections such as nomination patterns, terms of office, presidential requirements, and thresholds. However, in analyzing this difference, there are only two countries that are the same: Indonesia and Türkiye, for the same presidential term. Then the nomination pattern in Russia and Türkiye is the same. Then, the age requirements for Indonesian and Türkiye presidential candidates are the same